BOOK REVIEW: TEACHER DEVELOPMENT FOR IMMERSION AND CONTENT-BASED INSTRUCTION - Sabrina, Darayani; Dewi, Utami (LLT Journal: A Journal on Language and Language Teaching, 2024)
This review provides a concise overview of the book "Teacher Development for Immersion and Content-Based Instruction” by Laurent Cammarata and T. J. Ó Ceallaigh, published in 2020 by John Benjamins Publishing Company. The review highlights its significant contributions to the understanding of global language immersion programs. The book, which features significant input from respected scholars, focuses on filling the knowledge gaps regarding teacher development in the context of language immersion and content-based training. The book consists of seven chapters that address various subjects, including teacher language awareness, the development of professional identity, and the difficulties encountered by immersion educators. The review acknowledges the book's thorough approach but points out a possible omission in distinguishing between Content-Based Instruction and Content and Language Integrated Learning The review suggests that the book is a great resource for educators, academics, and policymakers. The extensive examination of both theory and practice renders it an invaluable resource for individuals engaged in language instruction and research.